Model Instantiation and Type Checking in UMLX - Willink, Edward (Electronic Communications of the EASST, 2006)
OMG’s MDA initiative encourages the use of meta-model based transformations and re-usable specifications. We discuss how Graphical Transformation Notations such as UMLX reduce opportunities for errors in this programming domain.